Democracy and Peace is Still in Process in Jammu And Kashmir - Rouf Shiekh, Ab. (International Journal of Psychosocial Rehabilitation, 2019)
Jammu and Kashmir, a contentious issue between two nuclear-powered states since 1947. The geographical area of Jammu and Kashmir is asymmetrically distributed between India and Pakistan. Both countries have tried to maintain the peace in their respective jurisdictions. India in particular has tried myriad models in order to maintain peace in the region. The restiveness in Kashmir has largely been fomented by its neighbour. Since the separatism began in Kashmir, New Delhi has used various mechanisms to absorb the secessionist tendencies in the valley, as has been the case with every large democracy around the world. These mechanisms include both iron-fist policies and a lot of soft authoritarian diplomacy. The convergence and divergence of peacebuilding exercises have seen a lot of highs and lows since 1947. This paper analyses those measures through peacebuilding lenses and what has been the overall trajectory of those efforts.